2019
DOI: 10.1088/1361-6528/aaf9e8
|View full text |Cite
|
Sign up to set email alerts
|

Mo2C/graphene heterostructures: low temperature chemical vapor deposition on liquid bimetallic Sn–Cu and hydrogen evolution reaction electrocatalytic properties

Abstract: Thin 2D Mo2C/graphene vertical heterostructures have attracted significant attention due to their potential application as electrodes in the hydrogen evolution reaction (HER) and energy storage. A common drawback in the chemical vapor deposition synthesis of these structures is the demand for high temperature growth, which should be higher than the melting temperature of the metal catalyst. The most common metallic catalyst is Cu, which has a melting temperature of 1084 °C. Here, we report the growth of thin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 48 publications
1
49
0
Order By: Relevance
“…However, this elevated temperature is unacceptable for many applications which has led to recent studies using Cu alloy substrates such as Cu-Sn to lower the growth temperature. 9 In this work the effects of using a Ag-Cu alloy as a substrate for Mo 2 C synthesis by chemical vapor deposition were systematically analyzed. The results conclusively demonstrated that synthesis of Mo 2 C is controlled by Mo diffusion through the liquid alloy ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…However, this elevated temperature is unacceptable for many applications which has led to recent studies using Cu alloy substrates such as Cu-Sn to lower the growth temperature. 9 In this work the effects of using a Ag-Cu alloy as a substrate for Mo 2 C synthesis by chemical vapor deposition were systematically analyzed. The results conclusively demonstrated that synthesis of Mo 2 C is controlled by Mo diffusion through the liquid alloy ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…In order to lower the CVD growth temperature of Mo2C crystals, alloys have been used. For this purpose, Cahitoglu et al 15 used a liquid bimetallic Sn-Cu alloy instead of Cu foil and showed that Mo2C could grow at temperatures as low as 880 °C with sizes of μm in diameter and hundreds of nm in thickness. Sun et al 16 used Au and very recently, Young et al…”
Section: Results Is the Formation Of 2mo + C  Mo2cmentioning
confidence: 99%
“…In this way, the temperature demand could be reduced to 880 • C, compared with the usual 1084 • C, and the cost of energy decreased without sacrificing the quality of the Mo 2 C/graphene film. The electrocatalyst also exhibited a better result than the pure Mo 2 C [116]. As the synthetic method has been developed, Mo 2 C, which is proved to be an excellent catalyst for HER, might also become low-cost and efficient OER electrocatalyst.…”
Section: Iron Carbidementioning
confidence: 97%